DMSO induces major morphological and physiological alterations in zebrafish embryos - Geyse Gomes; Allaina Christina de Sousa Andrade; Paloma de Carvalho Vieira; Murilo Nespolo Spineli; Manoel Luis Costa; Claudia Mermelstein (PLoS ONE, 2025)
Dimethyl sulfoxide (DMSO) is a polar aprotic solvent that dissolves both polar and nonpolar compounds and is miscible in a wide range of organic solvents as well as water. These characteristics render DMSO one of the most widely used solvents in pharmaceutical industry, as well in basic biomedical research, such as in developmental biology studies. The analysis of the effects of DMSO during the development of zebrafish larvae is particularly important since zebrafish is one of the most studied vertebrate models in developmental biology and in toxicology. It has been reported that DMSO at concentrations up to 1% are safe to be used in zebrafish embryo developmental toxicity assays, but fundamental questions such as whether and how different concentrations of DMSO affect the morphology and physiology of zebrafish have not been investigated. Therefore, our study focused on the analysis of DMSO treatment during zebrafish development using high resolution optical microscopy and real-time video-microscopy of the whole embryo, as well as focusing on some organs and tissues. Our results show that concentrations above 5% of DMSO are lethal to embryos, whereas concentrations between 1–4% induce different morphological and physiological alterations in embryos. The alterations observed include up-curved tail, heart beating frequency, heart edema, somite size, myofibril alignment, melanocyte size, notochord and swim bladder morphology. These results show for the first time a detailed analysis of the major effects of the widely used solvent DMSO during zebrafish development and call for attention in the use of DMSO in basic and applied research.